Negative thermal expansion in silicalite-1 and zirconium silicalite-1 having MFI structure - Bhange, Deu S.; Ramaswamy, V. (Materials Research Bulletin, 2006)
In situ high temperature X-ray diffraction (HTXRD) studies on monoclinic silicalite-1 (S-1, silica polymorph of ZSM-5) and an orthorhombic metallosilicate molecular sieve, zirconium silicalite-1 (ZrS-1) with MFI structure (Si/Zr = 50) have been carried out using a laboratory X-ray diffractometer with an Anton Parr HTK 1600 attachment. While the structure of the S-I collapsed at 1123 K forming alpha-cristobalite. S-1 and ZrS-1 showed a complex thermal expansion behavior in the temperature range 298-1023 K, ZrS-1 was stable. Powder X-ray diffraction (PXRD) data taken in this region have shown strong negative lattice thermal expansion coefficient, alpha(v) = -6.75 x 10(-6) and - 17.92 x 10(-6) K-1 in the temperature range 298-1023 K-1 for S-1 and ZrS-1 samples, respectively. The thermal expansion behavior of S-1 and ZrS-1 is anisotropic, with the relative strength of contraction along a axis is more than that along b and c axes. Three different thermal expansion regions could be identified in the overall temperature range (298-1023 K) studied, corroborating with the three steps of weight loss in the TG curve of ZrS-1 sample. While the region between 298 and 423 K, displays positive thermal expansion coefficient with alpha(v) = 2.647 x 10(-6) and 4.24 x 10(-6) K-1, the second region between 423 and 873 K shows strong negative thermal expansion (NTE) coefficient alpha(v) = -7.602 x 10(-6) and - 15.04 x 10(-6) K-1, respectively, for S-1 and ZrS-1 samples. The region between 873 and 1023 K, shows a very strong NTE coefficient with alpha(v) = - 12.08 x 10(-6) and -45.622 x 10(-6) K-1 for S-1 and ZrS-1, respectively, which is the highest in the whole temperature range studied. NTE seen over a temperature range 298-1023 K could be associated with transverse vibrations of bridging oxygen atoms in the structure which results in an apparent shortening of the Si-O distances. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: microporous materials; phase transitions; Thermal expansion; X-ray diffraction

NCL-7, a novel all silica analog of polymorph B rich member of BEA family: synthesis and characterization - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
{Polymorph B-rich BEA type structure, NCL-7, was synthesized using hydrothermal method in fluoride medium using perchloric acid as promoter. The samples were characterized using XRD, low temperature N-2-adsorption and Si-29 MASNMR. As the structure of beta is highly disordered Rietveld refinement of powder XRD patterns is precluded. Phase composition is derived using the simulated patterns for the random intergrowths of polymorph A and B by DIFFaX. The stacking direction c' is perpendicular to the a'b' plane of the layer. The composition of polymorph B is found to be ca. 60-65%. Two other structures namely NCL-5 and NCL-6 with varying degree of polymorph B enrichment were also synthesized. Synthesis parameters such as effect of H2O/SiO2, TEAOH/SiO2, HClO4/SiO2 and crystallization temperature were studied thoroughly. The present article explains for the first time the synthesis and characterization of NCL-7, an analog of BEA type family with enrichment of polymorph B and its comparison with normal beta (*
Keywords: B-polymorph; DIFFaX; Promoter; Reitveld refinement; synthesis; zeolite beta

Non-isothermal kinetic studies of the template decomposition from silicalite-1 framework-high temperature X-ray diffraction and thermogravimetric analysis - Bhange, Deu S.; Pandya, N. A.; Jha, Ratnesh Kumar; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
Non-isothermal decomposition of the tetrapropylammonium cations (TPA(+)) intercalated in silicalite-1 framework has been carried out using thermogravimetric (TG) analysis and high temperature powder X-ray diffraction (HTXRD) techniques. Conversion factor for template decomposition is calculated using two methods viz., % weight loss from the thermogravimetric analysis and changes in the intensities of the Bragg reflections 101/011 and 200/020 in the HTXRD patterns scanned at different temperatures (range 298823 K). The calculated apparent activation energy for template decomposition in air was 129 and 125 kJ mol(-1), respectively, for the two techniques TG and HTXRD, calculated using the Kissinger method. By Flynn-Wall-Ozawa approach of isoconversion, apparent activation energy for template decomposition in air was 123 and 124 U mol-1, respectively, for TG and HTXRD data. The reaction order was determined using the method of Kennedy and Clark and it is similar to 2 by both the techniques. The second order of template decomposition can be attributed to the fact that TPA+ is positioned in two different orientations inside the silicalite-1 framework. Template removal occurs with a contraction in unit cell dimensions. There is a decrease in the lattice parameters of the as-synthesized silicalite-1 sample after removal of template from the framework. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: HTXRD; non-isothermal kinetics; Silicalite-1